PENGARUH JUMLAH PEMBIAYAAN DAN NILAI JAMINAN TERHADAP KELANCARAN PENGEMBALIAN PEMBIAYAAN DI KSP MITRA RAKYAT KEDIRI - Tiara Dwi Tristiani (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2023)
The development of modern business is indeed challenging, especially in terms of financing. KSP Mitra Rakyat is a savings and loan cooperative that is willing to help meet the needs of the community. This cooperative has experienced a decline since the pandemic (Covid-19). This is because various client parties are unable to meet the amount of financing that has been lent. Guarantees that lack this value, this cooperative cannot meet the amount of financing provided to customers. This research is a quantitative research that aims to produce a discovery obtained through statistical procedures. The sample in this study used purposive sampling with 54 customers as respondents. The data in this study were obtained through survey results, interviews and questionnaires. The results of the study show that financing funds have an effect on partial loan repayment payments, the collateral value has an effect on the partial smooth repayment of financing, the financing value and the collateral value have an effect on the financing repayment loans simultaneously. This is evidenced by the results of the R Square value of 53.2%. While the rest (100% - 53.2% = 46.8%) is influenced by other variables outside the research.